Sub-Diagnostic Psychiatric Comorbidity in Alcoholics - Fein, George (2006)
BACKGROUND: Psychiatric comorbidity in alcohol use disorders is clearly established, however most studies ignore data on psychiatric symptom counts that do not meet criteria for a diagnosis. We examined psychiatric symptom counts and psychological measures in the domains of anxiety, mood and externalizing pathology in 48 long-term abstinent alcoholics (LTAA) compared to 48 age/gender comparable light/non-drinking controls(NC). METHODS: Continuous measures of pathology (i.e., symptoms counts and psychological assessments) in each domain were compared between groups for: 1) all study participants, 2) excluding individuals with a lifetime psychiatric diagnosis in the domain, and 3) excluding individuals with a current psychiatric diagnosis in the domain. RESULTS: Psychiatric symptom counts and psychological pathology were greater in LTAA than NC. The differences between groups on these measures were not reduced by removal of individuals with lifetime or current diagnoses. CONCLUSIONS: The bulk of the difference between LTAA and NC in psychiatric illness was carried by sub-diagnostic psychopathology. In comparison to the limited view provided by using only symptomatology that meets criteria for a diagnosis, the use of continuous measures of psychiatric symptomatology and psychological abnormality yields a much more accurate picture of psychiatric illness co-occurring with alcoholism.